(Na, Li)3(Cl, OH)[Cu3OAl(PO4)3]: a first salt‐inclusion aluminophosphate oxocuprate with a new type of crystal structure. Issue 1 (12th January 2023) - Yakubovich, Olga V.; Kiriukhina, Galina V.; Simonov, Sergey V.; Volkov, Anatoly S.; Dimitrova, Olga V.
Abstract : A new composite crystal structure is assembled from bands of Cu‐centered polyhedra, chains of AlO6 octahedra linked via PO4 tetrahedra, and includes an Na/Li salt component. Abstract : The synthesis and characterization of a first salt‐inclusion aluminophosphate oxocuprate, (Na, Li)3 (Cl, OH)[Cu3 OAl(PO4 )3 ], obtained as single crystals, is reported. A novel phase, with a strongly pseudo‐orthorhombic structure, is described as a monoclinic crystal structure established by the study of a pseudomerohedric microtwin. It was investigated using scanning electron microscopy, microprobe analysis and low‐temperature X‐ray diffraction. The composite crystal structure represents an original framework assembled from Cu‐centered polyhedra, AlO6 octahedra and PO4 tetrahedra with channels, which incorporate the Na/Li salt component [(Na, Li)3 (Cl, OH)] 2+ that ensures electroneutrality of the compound. Layers of strongly corrugated chains of Cu‐centered octahedra with shared edges and linked by PO4 tetrahedra are shown to be topologically identical with the layers also built from Cu‐centered polyhedra and AsO4 /VO4 tetrahedra forming the crystal structure of a fumarolic mineral aleutite, ( M 0.5 Cl)[Cu5 O2 (AsO4 )(VO4 )] [Siidra et al. (2019). MinMag, 83, 847–853]. `Sawtooth chains' and pairs of Cu‐centered octahedra inherent in the title structure may be of interest in solid‐state physics, engaging studies in the field of low‐dimensional and frustrated magnetism.